Broadcasting, Cable, the Internet and Beyond: An Introduction to Modern Electronic Media - DOMINICK, Joseph R (McGraw - Hill Book Company, 2000)
Broadcasting, Cable, The Internet, And Beyond : An Introduction to modern...